1995
DOI: 10.1111/j.1440-1827.1995.tb03437.x
|View full text |Cite
|
Sign up to set email alerts
|

Metanephric adenoma of the kidney

Abstract: A case of a rare renal tumor showing characteristic histologic features is presented. The patient was a 54 year old female, whose renal tumor was incidentally detected on abdominal ultrasound (US) examination. Ultrasound, computed tomography and angiography findings were consistent with a diagnosis of renal cell carcinoma of the hypovascular type. Left nephrectomy was performed. The tumor, which measured 2.6 x 2.6 x 2.5 cm, was located in the left renal cortex, and had a uniformly whitish-yellow cut surface an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 3 publications
(1 reference statement)
2
19
0
Order By: Relevance
“…Few ultrasound, CR or MRI findings have been described in the literature. However, the case reported by Nonomura et al 9 had findings similar to those of the present case; ultrasound revealed a hypoechoic mass with a small, irregurarly shaped hypoechoic area and non-contrast CT showed the tumor as an isodense mass that had increasing attenuation values after contrast medium infusion. Furthermore, the tumor was represented as an isointense mass on both T 1 -and T 2 -weighted MRI.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Few ultrasound, CR or MRI findings have been described in the literature. However, the case reported by Nonomura et al 9 had findings similar to those of the present case; ultrasound revealed a hypoechoic mass with a small, irregurarly shaped hypoechoic area and non-contrast CT showed the tumor as an isodense mass that had increasing attenuation values after contrast medium infusion. Furthermore, the tumor was represented as an isointense mass on both T 1 -and T 2 -weighted MRI.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, the tumor was represented as an isointense mass on both T 1 -and T 2 -weighted MRI. In the case reported by Nonomura et al, 9 a preoperative diagnosis of renal cell carcinoma of the hypovascular type was made according to these image findings. In the present case, there was no obvious sign of neovascularization of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Hypodense mass in the T1 weighted image, sometimes slightly hyperdense on the T2 weighted image was reported [18,28], as well as an isointense mass on both T1 and T2 weighted MRI scans. [14,30]. The case presented here, even appeared hypodense on the T2 weighted images.…”
Section: Discussionmentioning
confidence: 53%
“…Ultrasound images of metanephric adenoma have been described as hyperechoic [20] as well as hypoechoic [14,18,30]. Only one case was reported where ultrasound demonstrated a cystic renal mass, similar to the case presented here [22].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation